Keunikan Metode Tafsir Al-Quranil Azhim Al-Adzim Karya Ibnu Katsir - Nabilah Nuraini; Dinni Nazhifah; Eni Zulaiha (LPPAIK Universitas Muhammadiyah Bandung, 2022)
Ibn Kasir belongs to the Middle Ages Mufassir (8th century AH / 15th century AD), but in terms of methods and forms of interpretation, Ibn Kasir is in the